ANALYZING PREPOSITIONAL ERRORS "TO & FOR” COMMITTED BY UNDERGRADUATE STUDENTS FOR IRAQI EFL LEARNERS - Mohammed Hameed Rasheed (American Journals Publishing, 2024)
The main purpose of this paper is the basic applications between two English prepositions {To & For} using contrastive analysis. In this regard, it is assumed that second language learners struggle with preposition use. Thus, this study seeks to assess the performance of college students in applying prepositions involving prepositional errors {To & For} among undergraduates studying English as a Foreign Language in Iraq, can shed some light on the challenges encountered by learners when mastering correct usage. This study offers an in-depth understanding of the specific difficulties that Iraqi EFL learners encounter with these prepositions and proposes areas for instructional focus. However, prepositions are a vital component in English grammar. The correct usage of prepositions is important not only for the right communication but also in writing and speaking, too. This paper considered the pair {To and For} as words used frequently by many people who sometimes confuse them.